PELUANG DAN TANTANGAN METAVERSE SEBAGAI MEDIA PEMBELAJARAN SEJARAH: SEBUAH KAJIAN LITERATUR SISTEMATIS - Alim, Muhammad Rofiul (Jurnal Pendidikan Sejarah Indonesia, 2023)
Abstract: The metaverse technology was massively developed in the last decade. The utilization and development of the metaverse in the field of education is considered in line with the concept of society 5.0 and 21st century competencies. Innovation makes the learning process interactive by cultivating critical thinking, communication, creative thinking, and collaboration. The development of the metaverse in the field of education is an effort to present the concept of student center learning. This research method uses a literature review by collecting scientific studies, analyzing, and comparing the use and utilization of the metaverse in education. Data search procedures, data analysis, topic determination, literature review and conclusions related to the opportunities and challenges of the metaverse as a medium for learning history. Data analysis used a literature review with descriptive qualitative. The keywords in the literature search are "Metaverse" and "Learning Media" with a publication period of 2015-2023. The Opportunities for metaverse technology in the world of education have great opportunities to be developed to improve the quality of education. The presence of metaverse technology has challenges such as crime and digital data security and a lack of humanity. This needs to be balanced with an understanding of digital literacy so that it is the center of progress in human-centered society, science and technology. Abstrak:Teknologi metaverse masif dikembangkan dalam dekade belakangan. Pemanfaatan dan pengembangan metaverse dalam bidang pendidikan dinilai selaras dengan konsep masyarakat 5.0 dan kompetensi abad 21. Inovasi menjadikan proses belajar pembelajaran interaktif dengan menumbuhkan critical thinking, communication, creative thinking, and collaboration. Pengembangan metaverse pada bidang pendidikan menjadi upaya menghadirkan konsep pembelajaran student center. Metode penelitian ini menggunakan literature review dengan mengumpulkan kajian ilmiah, menelaah, dan membandingkan penggunaan dan pemanfaatan metaverse pada pendidikan. Prosedur pencarian data, analisis data, penentuan topik, literature review dan kesimpulan terkait peluang dan tantangan metaverse sebagai media pembelajaran sejarah. Analisis data menggunakan literatur review dengan kualitatif deskriptif. Kata kunci dalam pencarian literatur yakni “Metaverse” dan “Media Pembelajaran” dengan rentang waktu publikasi tahun 2015-2023. Peluang teknologi metaverse di dunia pendidikan memiliki peluang besar untuk dapat dikembangkan untuk meningkatkan kualitas pendidikan. Hadirnya teknologi metaverse memiliki tantangan seperti adanya kejahatan dan keamanan data digital dan kurangnya sisi kemanusiaan. Hal ini perlu diimbangi pemahaman literasi digital sehingga pusat kemajuan pada human-centered society, sains, dan teknologi.